2015
DOI: 10.2217/epi.15.45
|View full text |Cite
|
Sign up to set email alerts
|

HIF3A Association with Adiposity: The Story Begins Before Birth

Abstract: Aim:Determine if the association of HIF3A DNA methylation with weight and adiposity is detectable early in life.Material & methods:We determined HIF3A genotype and DNA methylation patterns (on hybridization arrays) in DNA extracted from umbilical cords of 991 infants. Methylation levels at three CpGs in the HIF3A first intron were related to neonatal and infant anthropometry and to genotype at nearby polymorphic sites.Results & conclusion:Higher methylation levels at three previously described HIF3A CpGs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 36 publications
5
81
6
1
Order By: Relevance
“…Dick et al 106 identified a correlation between increased BMI and hypermethylation at three CpG sites in the first intron of the HIF3A gene in blood cells and adipose tissue. These results were confirmed in both adults and children across bodyweight relevant cell types and diverse ethnic groups 106–110 . Additional differentially methylated sites were found that supported the relevance of epigenetic mechanisms in obesity.…”
Section: From Genomics To Epigenomicssupporting
confidence: 57%
“…Dick et al 106 identified a correlation between increased BMI and hypermethylation at three CpG sites in the first intron of the HIF3A gene in blood cells and adipose tissue. These results were confirmed in both adults and children across bodyweight relevant cell types and diverse ethnic groups 106–110 . Additional differentially methylated sites were found that supported the relevance of epigenetic mechanisms in obesity.…”
Section: From Genomics To Epigenomicssupporting
confidence: 57%
“…Increased BMI among adults was found to be positively associated with increased methylation at the hypoxiainducible factor 3 alpha (HIF-3α) locus in blood cells and adipose tissue [231]). This finding was confirmed in two replication cohorts in the initial analysis [231], as well as two additional independent studies [232,233]. A separate EWAS of an African American sample identified an association between methylation at 37 CpG sites and BMI, which were replicated in two cohorts of European ancestry [232].…”
Section: Biological Processes Underlying Statistical Gene-environmentmentioning
confidence: 57%
“…Long variants HIF1a/2a [33,39] MicroRNA [45] HIF1/2a, HIF1b [40] Inhibition of HIF1/2a mediated gene expression through the formation of an abortive transcriptional complex, when HIF1b is limiting [23,40] Induction of hypoxia-related and unrelated specific gene expression [40,[46][47][48] Differentiation of pulmonary epithelium and in alveologenesis [47] Angiogenic gene regulation in pulmonary endothelial cells [51] Role in the abnormal bone development in the genetic disease arthrogryposis type 2B [58] Potential causal relation between DNA methylation of HIF3a promoter and adiposity [54][55][56][57]…”
Section: Hif3a Variant Induced By Repressed By Interacts With Activitiesmentioning
confidence: 99%